2020
DOI: 10.1002/etc.4850
|View full text |Cite
|
Sign up to set email alerts
|

Mean Species Abundance as a Measure of Ecotoxicological Risk

Abstract: Chemical pollution of surface waters is considered an important driver for recent declines in biodiversity. Species sensitivity distributions (SSDs) are commonly used to evaluate the ecological risks of chemical exposure, accounting for variation in interspecies sensitivity. However, SSDs do not reflect the effects of chemical exposure on species abundance, considered an important endpoint in biological conservation. Although complex population modeling approaches lack practical applicability when it comes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Therefore, in addition to toxicity-based considerations of species sensitivity to compounds, species richness and ecosystem functions should be considered. One approach developed by Hoeks et al . uses species-specific exposure-response models with population growth concepts to assess the effects of chemical exposures on mean species abundance.…”
Section: Challenges and Ways Forwardmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in addition to toxicity-based considerations of species sensitivity to compounds, species richness and ecosystem functions should be considered. One approach developed by Hoeks et al . uses species-specific exposure-response models with population growth concepts to assess the effects of chemical exposures on mean species abundance.…”
Section: Challenges and Ways Forwardmentioning
confidence: 99%
“…Therefore, in addition to toxicity-based considerations of species sensitivity to compounds, species richness and ecosystem functions should be considered. One approach developed by Hoeks et al 34 uses species-specific exposure-response models with population growth concepts to assess the effects of chemical exposures on mean species abundance. While this approach is more constrained by data availability than traditional SSD-based approaches, it shows promise for incorporating species richness into chemical effect endpoints.…”
Section: Identifying Relevant Chemicalsmentioning
confidence: 99%
“…While the focus of most computational approaches assessing species’ sensitivity to chemical exposures characterize sensitivity across species rather than changes in abundance, one preliminary approach to estimate how chemical exposures may alter species abundance is the mean species abundance relationship (MSAR) . Preliminary estimates of species abundance can also be developed using probabilistic approaches to model different ratios of species abundance to assess potential biodiversity impacts.…”
Section: The Need For Computational Methods To Assess Chemical Impact...mentioning
confidence: 99%
“…While the focus of most computational approaches assessing species' sensitivity to chemical exposures characterize sensitivity across species rather than changes in abundance, one preliminary approach to estimate how chemical exposures may alter species abundance is the mean species abundance relationship (MSAR). 56 Preliminary estimates of species abundance can also be developed using probabilistic approaches to model different ratios of species abundance to assess potential biodiversity impacts. Other approaches can harness existing data sets on species occurrence (e.g., data in GBIF) to build ML and/or statistical methods to predict species occurrence (or distributions of occurrence) in different ecosystems (i.e., cross-region extrapolation).…”
Section: Ecosystem Diversitymentioning
confidence: 99%
“…Just as intraspecific concentration-response relationship parameters (EC 50 , β) can be related to population dynamics of a species, one may mechanistically and statistically link interspecies sensitivity distributions quantities (HC 50 , β) to community development. Initial attempts demonstrated that the potentially affected fraction (PAF) of species as described above can be related to the mean species abundance (MSA an often-used indicator in global change studies (Hoeks et al, 2020). Even more, impact of pesticides on MSA as calculated from PAF was confirmed by a decrease of macrofauna abundance in the field (Thunnissen et al, 2020; 2022).…”
Section: Ecological Variabilitymentioning
confidence: 99%